Pengaruh Karakteristik Risk Committee terhadap Financial Stability: Studi pada Bank Umum di Indonesia yang Terdaftar di Bursa Efek Indonesia - Nabila Indah Azhari; Mayar Afriyenti (Universitas Negeri Padang, 2026)
This study aims to examine the effect of Risk Committee Characteristic on Finansial Stability (study on public banking companies in Indonesia listed on the Indonesia Stock Exchange for 2019-2023 period). The population of this research is public banking companies in Indonesia listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sample was determined using purposive sampling technique and then resulted in 46 public banking companies as samples. The source of data in this research is secondary data from banking annual and GCG reports. Data analysis using multiple linier regression analysis, using the SPSS version 26 program. Finansial stability as the dependent variable are measured by z-score. The characteristics of the risk committee (RC) used in this research are the RC size, RC activity, RC expertise, and RC independence. This study is equipped with a control variable, namely bank size and leverage. The result showed that the characteristics of the risk committee and bank size has no effect on the finansial stability of public banking in Indonesia listed on the Indonesian Stock Exchange, mean while leverage has a positive effect on finansial stability of public banking listed on the Indonesia Stock Exchange.